THE EFFECT OF GLYCERIN APPLICATION ON SURFACE HARDNESS OF NANOHYBRID COMPOSITE RESIN IMMERSED IN ALCOHOLIC MOUTHWASH - Tio Aldi Nugroho; Gloria Fortuna; Lusiana Batubara; Nadia Hardini (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACT Background: Composite resin is the most commonly used restorative material. One of properties composite resins is surface hardness can change due to exposure of the restorative material to oral fluids such as alcoholic mouthwash. The degradation that occurs due to alcoholic mouthwash is able to reduce the surface hardness of the nanohybrid composite resin. Glycerin is able to increase the hardness of the composite resin by perfecting the polymerization that occurs in the restorative material when exposed to light cured light. Objectives: This study aims to determine the effect of glycerin application on the hardness of nanohybrid composite resins after immersion in alcoholic mouthwash. Methods: A total of 32 samples of nanohobride composite resin in this study were made in the form of a cylinder with a diameter of 5 mm and a thickness of 2 mm. The nanohybrid composite resin samples were divided into control and treatment group by applying glycerin on the sample surface before light curing. The study was continued by immersing the sample into artificial saliva for 24 hours and alcoholic mouthwash for 6 hours. The research continued with surface hardness test using the Vickers Hardness Tester. Result : Paired bivariate T test showed a significant difference between the two groups (p<0.005). The conclusions of this study indicate that the application of glycerin has an effect on the hardness of the nanohybrid composite resin after immersion with alcoholic mouthwash. Conclusion: The application of glycerin affects the hardness of the nanohybrid composite resin after immersion with alcoholic mouthwash.  Key words: Glycerin application, Hardness, Nanohybrid composite resin